Promoting Roles of Melatonin in Adventitious Root Development of Solanum lycopersicum L. by Regulating Auxin and Nitric Oxide Signaling - Dan eWen (Frontiers in Plant Science, 2016)
Melatonin (MT) plays integral roles in regulating several biological processes including plant growth, seed germination, flowering, senescence and stress responses. This study investigated the effects of MT on adventitious root formation (ARF) of de-rooted tomato seedlings. Exogenous MT positively or negatively influenced ARF, which was dependent on the concentration of MT application. In the present experiment, 50 µM MT showed the best effect on inducing ARF. Interestingly, exogenous MT promoted the accumulation of endogenous nitric oxide (NO) by down-regulating the expression of S-nitrosoglutathione reductase (GSNOR). To determine the interaction of MT and NO in ARF, MT synthesis inhibitor p-chlorophenylalanine, NO scavenger 2-(4-carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide potassium salt as well as GSNOR-overexpression plants with low NO levels were used. The function of MT was removed by NO scavenger or GSNOR-overexpression plants. However, application of MT synthesis inhibitor did little to abolish the function of NO. These results indicate that NO, as a downstream signal, was involved in the MT-induced ARF. Concentrations of indole-3-acetic acid and indole-3-butyric acid, as well as the expression of several genes related to the auxin signaling pathway (PIN1, PIN3, PIN7, IAA19 and IAA24), showed that MT influenced auxin transport and signal transduction as well as auxin accumulation through the NO signaling pathway. Collectively, these strongly suggest that elevated NO levels resulting from inhibited GSNOR activity and auxin signaling were involved in the MT-induced ARF in tomato plants. This can be applied in basic research and breeding.